2020
DOI: 10.1371/journal.pone.0240781
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, risk factors and clinical course of SARS-CoV-2 infected patients in a Swiss university hospital: An observational retrospective study

Abstract: Background This study aims to describe the epidemiology of COVID-19 patients in a Swiss university hospital. Methods This retrospective observational study included all adult patients hospitalized with a laboratory confirmed SARS-CoV-2 infection from March 1 to March 25, 2020. We extracted data from electronic health records. The primary outcome was the need to mechanical ventilation at day 14. We used multivariate logistic regression to identify risk factors for mechanical ventilation. Follow-up was of at l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…A total of 1595 studies were screened; only thirty observational studies met the final inclusion criteria in the analysis ( Figure 1 ; Table A1 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Main study characteristics of COPD and asthma analysis cohorts are abridged in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1595 studies were screened; only thirty observational studies met the final inclusion criteria in the analysis ( Figure 1 ; Table A1 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Main study characteristics of COPD and asthma analysis cohorts are abridged in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Most of these clinical symptoms are associated with the respiratory system, specifically the lungs, resulting in the depleted lung functionality 2 . Several risk factors for severe COVID-19 disease, such as the age, sex, and obesity have been identified 3 . However, more research is needed to better understand the involvement of these and other risk factors in severe illness or complications.…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, asthma did not feature as a comorbidity associated with a higher mortality risk from SARS-CoV-2 24 . Similarly, a small Swiss study reported a 4% prevalence of asthma amongst hospitalized SARS-CoV-2 patients 25 . These data have not yet been extrapolated locally.…”
Section: Discussionmentioning
confidence: 95%